DESCRIPTION OF PHYSICAL ENVIRONMENTAL FACTORS, CHARACTERISTICS OF INDIVIDUALS, USE OF PPE AND IRRITANT CONTACT DERMATITIS IN BRATANG COMPOST HOUSES - Irfan Hamidi (Universitas Airlangga, 2022)
Introduction: Compost house is one of the government's efforts to overcome the adverse effects of increasing the volume of waste; one of the large compost houses is the Bratang Compost House. One of the health risks faced by workers is irritant contact dermatitis. The purpose of this study was to individual characteristics and use of PPE with the incidence of irritant contact dermatitis in workers at the Bratang Compost House. Methods: The study was descriptive observational with a cross-sectional model. Calculation of RR values was used to see the characteristics of the relationship between the use of PPE and the incidence of irritant contact dermatitis in workers at the Bratang Compost House. Result: The results showed that there were 9 workers affected by irritant contact dermatitis and 6 workers who were not affected by irritant contact dermatitis. Most workers affected by irritant contact dermatitis were dominated by workers age less than 30 years old and have a service life of more than 5 years. The results of the calculation of RR values indicated that poor usage of PPE can increase the risk of developing irritant contact dermatitis. Conclusion: What needs to be done by workers is to increase awareness of the importance of occupational health and safety especially the usage of PPE. The thing that needs to be done by the manager of the compost house is to fix the physical environmental factors, conduct socialization of health risks in the workplace and provide PPE to improve the safety of workers.